Fusarium pada Tanaman Jagung dan Pengendaliannya dengan Memanfaatkan Mikroba Endofit - Suriani Suriani; Amran Muis (Puslitbang Tanaman Pangan, 2016)
Endophytic microbes reside in the tissue of living plant. They can be isolated from the root, stems and leave of plant. Utilization of endophytic microbes for biological control of plant pathogens has been applied for some times. The ability to compete for space and nutrients and antibiotic production are the two main considerations for the use of endhopytic microbes as biological control to plant pathogens. Several species of endophytic microbes isolated from maize either from the class of fungi, bacteria or actinomycetes include Trichoderma spp., PenIicillium sp., Bacillus spp., dan Altenaria alternata. The microbes have been reported by some researchers to be effectively suppressing the development of pathogens Fusarium spp. which causes stem rot, cobs and grain maize. Endophytic microbes have a good prospect to be developed as maize disease control because they are affordable and environmentally friendly.